Short sludge age denitrification as alternative process for energy and nutrient recovery. (December 2022) - Tirkey, Vishal; Goonesekera, Estelle M.; Kovalovszki, Adam; Smets, Barth F.; Dechesne, Arnaud; Valverde-Pérez, Borja
Graphical abstract: Highlights: Short SRT denitrifying activated sludge system fully denitrified at 3 days SRT. Low sludge volume index (<25 mL mg −1 ) was achieved after sludge degassing. Sludge yields were comparable to the aerobic high rate activated sludge system. Produced sludge had higher methane yield than conventional activated sludge. Protein content was in the low range for aerobic high rate activated sludge systems. Abstract: High rate activated sludge (HRAS) systems redirect organics into highly biodegradable sludge and nutrients into microbial proteins. This study evaluates anoxic HRAS for nitrogen and carbon recovery. The reactor treated synthetic wastewater at solids retention times (SRTs) of 5, 3 and 1 days. Denitrification rates varied between 0.15 and 0.19 g-NO3 -N g-TSS -1 d -1 (total suspended solids per day) and all conditions showed favourable settling. The highest sludge yield, obtained at SRT 1 d, was 0.75 g-TSS g-CODremoved -1, double that observed for aerobic HRAS. The highest methane yield (322 mL-CH4 g-VSsludge -1 ) was obtained from sludge wasted at 3 d SRT. Both 1 d and 3 d SRTs showed favourable energy recovery, with 14 % of the organics recovered as methane. All conditions yielded sludge with protein content ranging between 24 and 27 % of dry weight and similar amino acid profile, comparable to traditional proteins. Thus, denitrifying HRAS recovers resources as its aerobic counterpart, allowing for nitrogen removal via denitrification, more stable compared to mainstream partial nitritation anammox typically combined with aerobic HRAS.